Visible light promoted Fe3S4 Fenton oxidation of atrazine - Shi, Yanbiao; Wang, Xiaobing; Liu, Xiufan; Ling, Cancan; Shen, Wenjuan; Zhang, Lizhi (Applied catalysis. B, Environmental, 2020)
[Display omitted] •Visible light could promote Fe3S4 Fenton oxidation of atrazine by 4.9 times.•The promoted activity was attributed to the efficient surface iron redox cycle.•The efficient surface iron redox cycle was triggered by visible light.•The formation of FeOOH accounted for poor Fenton activity of Fe3S4 in dark.•Visible light excited Fe3S4 to produce photo-generated electrons and O2−. We demonstrate that visible light irradiation can promote Fe3S4 Fenton oxidation of atrazine. The visible light irradiation could increase the atrazine Fenton degradation rate by 4.9 times. The enhanced atrazine degradation activity under visible light was attributed to the higher surficial Fe(II)/Fe(III) ratio of Fe3S4 and the efficient surface iron redox cycle triggered by visible light. Experimental results revealed that the operando formation of FeOOH on the Fe3S4 surface blocked the iron redox cycle and inhibited the H2O2 decomposition, accounting for the largely decreased Fenton activity of Fe3S4 in dark, while these problems were successfully solved by the introduction of visible light irradiation, which excite Fe3S4 to produce abundant photo-generated electrons and O2− for efficient regeneration of active Fe(II) species of Fe3S4 and in-situ formed FeOOH.